PENGEMBANGAN DAN INOVASI PASAR HUTAN BAMBU TO`KUMILA - Ferayanti Boas Gallaran; Israel Padang; Semuel Yakobus Padang; Bergita Gela Saka; Gidion Aryo Nugraha Pongdatu; Ariyen Duri (STKIP Persada Khatulistiwa Sintang, 2026)
ABSTRACTSustainable tourism development increasingly focuses on integrating nature-based tourism (ecotourism) and cultural heritage (cultural tourism). To'Kumila Bamboo Forest Market in Tonga Riu Village, North Toraja Regency, holds strong ecological and cultural potential; however, its management faces challenges including limited physical infrastructure, lack of MSME product innovation, and underutilized digital marketing. This community service program aims to enhance tourism appeal and local economic capacity through nature- and culture-based market innovations. The methodology employed a participatory approach, community empowerment, and educational interventions involving market managers, 16 local MSME actors, villagers, and tourists. Program implementation comprised socialization, hospitality training, physical site enhancement using bamboo-based green architecture, implementation of a unique bamboo token (